1999
DOI: 10.3130/aija.64.83_3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Structure of Water Demands in Dwelling Houses of Suzhou, China

Abstract: Currently , in China , the condit 正 on of water shortage has becn frequently happened in city 、 The water demand in city is largely increas ¢ d and the water supply shor 【 age problem is coming out because ofthe remarkable economic deve且 opment , the increase of populatien by urbanization and the 正 mprovement of living standard . Then, the unbaiance problem between water supply and demand is becoming more serious . Therefbre , the purpose of this study is to clarify the actual situation of water usage and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Thus, water demand in summer is 1.2 times that of the winter demand. This seasonal tendency is consistent with the published data in, for example, Suzhou, China (Murakawa et al, 1999). The annual per capita water use in Tokyo is 232 L, similar to that in Beijing.…”
Section: Household Water Uses and Behaviorsupporting
confidence: 80%
See 3 more Smart Citations
“…Thus, water demand in summer is 1.2 times that of the winter demand. This seasonal tendency is consistent with the published data in, for example, Suzhou, China (Murakawa et al, 1999). The annual per capita water use in Tokyo is 232 L, similar to that in Beijing.…”
Section: Household Water Uses and Behaviorsupporting
confidence: 80%
“…The monthly water rate for households with monthly income of less than 1,000 yuan was about 16 yuan, while that for households with a monthly income of over 1,000 yuan was 20 to 30 yuan. Previous investigations had shown that household income was proportional to the amount of water use (Murakawa et al, 1999;Zhang and Brown, 2005). In this study, the impact of income to water consumption could also be observed, although it was not so significant.…”
Section: Household Socioeconomic Characteristicsmentioning
confidence: 52%
See 2 more Smart Citations